(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Reproductive capability in a young woman begins at the point of menarche, which is the beginning of cyclic uterine bleeding in the anatomically and physiologically normal female. Menarche marks the beginning of an important stage in a young woman’s physical reproductive maturation and development. Even before the onset of this entirely natural but potentially disturbing function, a young woman’s early psychological reactions to menstruation, and probably also her lifelong view, can be influenced by the accuracy of her information and the degree of empathy with which this knowledge has been conveyed to her. Many women, perhaps appropriately, conclude that any departure from their personal menstrual experience is abnormal, and they will seek treatment for these departures. Conversely, some women accept or perhaps ignore even significant variations in their menstrual function, sometimes to the extent that serious health impairment occurs (e.g., severe iron-deficiency anemia). Therefore in this study an effort has been put forth to make a conceptual study covering almost all the aspect of Raktapradar as per Ayurvedic and modern.